RETROSPECTIVE ANALYSIS OF REPORTED CASE OF ADVERSE DRUG REACTION - NEUROLEPTIC MALIGNANT SYNDROME ON THE USE OF HALOPERIDOL - V. V. Arkhipov; N. G. Berdnikova; M. V. Zhuravleva; V. G. Kukes (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
This article provides a retrospective analysis of a case of adverse drug reactions to the drug haloperidol - neuroleptic malignant syndrome. A literature review on the issue of neuroleptic malignant syndrome was represented. The factors that led to this syndrome development of a particular patient were evaluated. Detailed clinical and pharmacological value of gene polymorphism CYP 2D6 is discussed. The data on the successful use of a therapy of neuroleptic malignant syndrome with ethylmethylhydroxypyridine malat are presented.